Implementation of Interactive Educational Games to Enhance Reading Literacy Skills of Elementary School Students - selviana, Herwinda ayu; Haifaturrahmah, Haifaturrahmah; Syafruddin Muhdar, Syafruddin Muhdar (AR-RIAYAH: Jurnal Pendidikan Dasar, 2025)
This study aimed to examine the implementation of interactive educational games as a means of enhancing reading literacy skills among elementary school students through the application of the Systematic Literature Review (SLR) method. Therefore, this study highlights the importance of teacher training and the development of supporting infrastructures to ensure the successful integration of interactive educational games in enhancing reading literacy at the elementary school level. The review revealed that interactive educational games, including Word Wall and other technology-based platforms, exerted a positive and significant impact on students’ reading proficiency. These games effectively promoted motivation, engagement, and comprehension during the learning process while simultaneously creating a more enjoyable and contextualized learning environment. Furthermore, the use of interactive educational games strengthened students’ understanding of textual content and fostered greater interest in literacy activities. Despite these benefits, the implementation of interactive educational games still faced several challenges, particularly related to limited digital infrastructure, teachers’ readiness, and the availability of school resources. Therefore, this study highlights the importance of teacher training and the development of supporting infrastructures to ensure the successful integration of interactive educational games in enhancing reading literacy at the elementary school level.